Race, ethnicity, and racism in the nutrition literature: an update for 2020. Issue 6 (3rd December 2020) - Duggan, Christopher P; Kurpad, Anura; Stanford, Fatima C; Sunguya, Bruno; Wells, Jonathan C
ABSTRACT: Social disparities in the US and elsewhere have been terribly highlighted by the current COVID-19 pandemic but also an outbreak of state-sponsored violence. The field of nutrition, like other areas of science, has commonly used 'race' to describe research participants and populations, without the recognition that race is a social, not a biologic, construct. We review the limitations of classifying participants by race, and recommend a series of steps for authors, researchers and policymakers to consider when producing and reading the nutrition literature. We recommend that biomedical researchers, especially those in the field of nutrition, abandon the use of racial categories to explain biologic phenomena but instead rely on a more comprehensive framework of ethnicity; that authors consider not just race and ethnicity but many social determinants of health, including experienced racism; that race and ethnicity not be conflated; that dietary pattern descriptions inform ethnicity descriptions; and that depersonalizating language be avoided.